Pelatihan dan Pendampingan Penyusunan SOP Pelayanan Bagi Pedagang di Pasar Kertasari, Kabupaten Badung - Giantari I G. A. Ketut; Sukaatmadja I Putu Gde; Ekawati Ni Wayan; Adnyani Dewi I G. A; Kerti Yasa Ni Nyoman; Purbadharmaja Ida Bagus Putu; Tirtayani I Gusti Ayu (Akademi Farmasi YPPM Mandiri, 2022)
This community service is carried out against the background of the wishes of the market head and traders who want to give satisfaction to buyers who shop at the Kertasari market. To give satisfaction to buyers, one way that can be taken is to provide the best service. Therefore, the purpose of this service is to provide understanding to market leaders and traders about the process of providing the best quality service. This service is in the form of a day training with resource persons: Dr. I Putu Gde Sukaatmadja, SE, MP, and continued with weekly consultations or mentoring after 2 times of training. This service takes place in the Kertasari Market, Badung Regency. After the service is carried out, the traders know the Standard Operating Procedure (SOP) of service, from greeting, serving with a smile, to saying thank you. If it can be implemented properly, then buyer satisfaction at the Kertasari Market, Badung Regency will increase.